Low-cost Colonoscopic Simulator and Colonoscope to Train Basic Skills in Colonoscopy during Undergraduate Studies - de Pinho, João Henrique Sendrete; Riscado, Lorrane Vieira Siqueira; Sales, Marcos Paulo Moreira; de Souza, Gabriel Seixa; de Castro, Abner Ramos; Bechara, Cristiane de Souza (Journal of Coloproctology, 2022)
Objective To develop a low-cost simulator model and a colonoscope with materials that are easily accessible to offer training on colonoscopy skills during undergraduate studies. Since this is the procedure of choice for colorectal cancer screening, the general practitioner must be able to recognize its main indications, preparation, and complications.Methods Using materials such as a mannequin, a vehicle inspection camera, a conduit, polyvinyl chloride (PVC) pipe, acrylic, wood, and red paint, we built a simulator and a 150-cm long and 20-to-25-mm thick colonoscope. The colonoscope's handle and handhold were made of acrylic, the colonoscope's mobile end was made with articulated PVC rings, and the up and down movements were performed according to the traction of the steel cables. The camera attached to its distal end enables connection to a smartphone to view the image. In the simulator, the conduit was inserted into the mannequin to simulate the curvatures of the colon. Red spray paint was used to simulate the staining of the colonic mucosa in the inner region of the mannequin and the adventitial layer in the outer region.Results We were able to build a simulator and a colonoscope with a total amount of R$ 182.82 (roughly US$ 36.50). Both were tested and proved to be useful in the acquisition of psychomotor and cognitive skills in colonoscopy.Conclusion The simulator and colonoscope developed by us are cost-effective, useful in the acquisition of psychomotor and cognitive skills in colonoscopy, and can facilitate the structuring of a training program for undergraduate students.
Keywords: colonoscopy; simulation; colonoscope; simulator; medical education